Rainfall Thresholds Analysis for Early Warning of Landslides in The Bompon Watershed - Ulul Albab, Milya Aflah; Nugroho, Bayu Dwi Apri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The transitional zone between the central and southern morphologies of Java is characterized by steep slopes and thick soil. On the other hand, high rainfall in the area poses a potential threat of landslide hazards. This research is conducted in the Bompon Watershed, located in the transitional zone between Mount Sumbing and the Menoreh Mountains. This study aims to examine the rainfall dynamics leading to landslides in the Bompon Watershed using rainfall threshold analysis. Intensity and duration are selected as parameters to establish the rainfall threshold model. The research findings indicate that long-duration rainfall is the dominant cause of landslides in the Bompon Watershed. High-intensity rainfall can trigger landslides when lasting for more than one day. The established rainfall threshold equation in the Bompon Watershed is I = , where I is intensity and D is duration. The effects of long-duration rainfall include raising the groundwater level, thereby increasing the slope load. The presence of clay in the Bompon Watershed can hinder proper rainwater infiltration. Poorly infiltrated water adds to the slope load and induces slope instability. The calculated rainfall threshold can serve as the basis for early landslide warning systems. Keywords: Landslide, Rainfall threshold, Bompon watershed, Rrainfall intensity, Rainfall duration